Modeling Anxiety Disorders Among Adolescent Working Women Across Various Sectors in Coimbatore: A Nano Topological Space Theory Approach - S.Divya; S.Santhiya; S.Akila; M.Gowri Manohari; P.Dhavamani; N.Sujithra (Utilitas Mathematica, 2025)
Anxiety disorders are the most common mental illness among teenagers occurring in 4.4 percent- age of 10-14 year olds and 5.5 percentage of 15-19 yearolds. Depression affects this population as well with shared symptoms including mood swings and withdrawal from others, tending to interfere with school atten- dance and heighten risk of suicide. Classical statistical approaches are not adequate to capture overlapping interwoven nature of these factors.This research presents a new application of nano topological space theory to simulate fine grained interrelations between variables for anxiety risk in young and adult women. We employ nano open sets and boundaries to chart fine grained uncertainties associated with hormone changes, stress at work,trauma and social support. Our aim is to delineate highrisk zones and hotspots to facilitate more individualized and targeted intervention.